To calculate \(-17 \times (-61)\):
When you multiply two negative numbers, the result is positive. Therefore:
\[ -17 \times -61 = 17 \times 61 \]
Now let's calculate \(17 \times 61\):
\[ 17 \times 61 = 1037 \]
So, the answer is:
1,037.
-1,037
78
1,037
-78
1 answer
To calculate \(-17 \times (-61)\):
When you multiply two negative numbers, the result is positive. Therefore:
\[ -17 \times -61 = 17 \times 61 \]
Now let's calculate \(17 \times 61\):
\[ 17 \times 61 = 1037 \]
So, the answer is:
1,037.